Geochemistry and mineralogy of wastes from lithium-bearing granite-pegmatite mining: resource potential and environmental risks - Hudson-Edwards, Karen A. (Frontiers in Geochemistry, 2024)
The global need for lithium (Li) is increasing due to its use in batteries which are used to make electric vehicles, wind turbines and fuel cells to facilitate the world’s ‘green transition’ to low carbon economies. The mining of Li, like that of other earth materials, produces large volumes of waste such as tailings and processing chemicals. A growing body of research is addressing the resource potential and environmental impacts of wastes from mining of Li-bearing granites and pegmatites that produce around 40 % of the world’s Li. The wastes are dominated by SiO2 and Al2O3, with lesser Na2O, K2O and Fe2O3, that are hosted in quartz, feldspar and micas. They can contain around 1 wt. % Li2O that is found in residual spodumene, lepidolite and zinnwaldite, and trace (<1 wt. %) amounts of Rb, Cs, U and Be. Some exploitation of the Li from granite-pegmatite tailings is occurring on a commercial scale. There is also good potential for the waste quartz, feldspar and mica to be used in ceramics and building materials, and for the Rb, Cs and Be to be used for photovoltaic cells, alloys and other applications. Spodumene-bearing wastes can contain potentially toxic and/or radioactive U, Th and Tl, but the concentrations are generally low. Overall, Li-bearing granite-pegmatite mine wastes have good potential to be reused, remined and recycled. More research is required to characterize their geochemistry and mineralogy in detail to improve recovery and to understand how processing and weathering may affect environmental risk.